PHYTONEMATODES OF THE APRICOT (PRUNUS ARMENIACA) IN THE SOUTHERN REGIONS OF THE SURKHANDARYA REGION OF UZBEKISTAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article provides data on the fauna and distribution of phytonematodes in the root soil and root system of apricot plants in the southern regions of the Surkhandarya region of Uzbekistan. In the fauna of phytonematodes in apricot plants, numerous species were Cephalobus persegnis, Chiloplacus sclerovaginatus, Ch.quintastriatus, Panagrolaimus rigidus, Aphelenchus avenae, Aphelenchoides parietinus, A.composticola, A.limberi, A.blasthophthorus, A.graminis, Helicotylenchus erythrinae, Pratylenchus pratensis and Ditylenchus dipsaci.